v₁ =910 m/s
m₂=1000 kg
v₂=10000 m/s
u= 1000 m/s
m₁=?
(m₁+m₂)u = m₁v₁ +m₂v₂
m₁=m₂(v₂-u)/(u-v₁)=
=1000(10000-1000)/(1000-910) = 100000 kg
a spaceship is moving at 1000 m/s release a satellite of mass 1000 kg at a speed of 10 000 m/s. what is the mass of the spaceship if it slows down to a velocity of 910 m/s?
9 answers
989
Efg
A spaceship moving at 1000 m/s releases a satellite of mass
1000 kg at a speed of 10 000m/s. What is the mass of the
spaceship if it slows down to a velocity of 910 m/s?
answer=91kg
1000 kg at a speed of 10 000m/s. What is the mass of the
spaceship if it slows down to a velocity of 910 m/s?
answer=91kg
I don't know
111.2
91kg
100000kg
The correct answer is 91 kg. Here's how to solve it:
Let's call the mass of the spaceship "m". According to conservation of momentum, the total momentum of the spaceship-satellite system before and after the satellite is released must be the same. We can use this fact to solve for "m".
Before the satellite is released, the momentum of the spaceship-satellite system is:
p1 = m * v1
where v1 = 1000 m/s is the velocity of the spaceship before the satellite is released.
After the satellite is released, the momentum of the spaceship-satellite system is:
p2 = m * v2 + m2 * v2'
where v2 = 910 m/s is the final velocity of the spaceship (after it has slowed down), v2' = 10,000 m/s is the velocity of the satellite relative to the spaceship, and m2 = 1000 kg is the mass of the satellite.
Since momentum is conserved, we have:
p1 = p2
or
m * v1 = m * v2 + m2 * v2'
Solving for "m", we get:
m = m2 * (v2' - v1) / (v1 - v2)
Plugging in the given values, we get:
m = 1000 kg * (10,000 m/s - 1000 m/s) / (1000 m/s - 910 m/s) = 91 kg
Therefore, the mass of the spaceship is 91 kg.
Let's call the mass of the spaceship "m". According to conservation of momentum, the total momentum of the spaceship-satellite system before and after the satellite is released must be the same. We can use this fact to solve for "m".
Before the satellite is released, the momentum of the spaceship-satellite system is:
p1 = m * v1
where v1 = 1000 m/s is the velocity of the spaceship before the satellite is released.
After the satellite is released, the momentum of the spaceship-satellite system is:
p2 = m * v2 + m2 * v2'
where v2 = 910 m/s is the final velocity of the spaceship (after it has slowed down), v2' = 10,000 m/s is the velocity of the satellite relative to the spaceship, and m2 = 1000 kg is the mass of the satellite.
Since momentum is conserved, we have:
p1 = p2
or
m * v1 = m * v2 + m2 * v2'
Solving for "m", we get:
m = m2 * (v2' - v1) / (v1 - v2)
Plugging in the given values, we get:
m = 1000 kg * (10,000 m/s - 1000 m/s) / (1000 m/s - 910 m/s) = 91 kg
Therefore, the mass of the spaceship is 91 kg.